PEMBERIAN PROGRAM SPECIAL IMMIGRANT VISA AMERIKA SERIKAT BAGI WARGA NEGARA AFGHANISTAN TAHUN 2009-2014 - Indraswari, Desak Ketut; Dharmiasih, D.A Wiwik; Nugraha, A.A. Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
9/11 brought  a considerable  impact on international security, especially for United States. Post 9/11, US declared Global War on Terrorism and war in Afghanistan  to arrest the perpetrators  of 9/11. US also made changes in their immigration  policy.  This  research  analyzes  the purpose  of US in  providing Special Immigrant Visas (SIV) program for citizens of Afghanistan in 2009-2014. SIV program  is certainly contradictory with US’s policy post 9/11. This issues discussed by answering the question to why the US provide SIV for citizens of Afghanistan. Data for this study were collected from various sources including: literary sources, news and reports, thenanalyzed with national interest, national strategic and foreign policytheoriticalframeworks.  The analysis  shows  that US provide  SIV program  to recruit citizens of Afghanistan  in achieving the US’s goals on Afghanistan war. SIV program serves as an attraction and appreciation of Afghan citizens who have helped US in Afghan war.   Keywords: Terrorism, Special Immigrant Visa, National Interest, National S t r a t e g y , Fo r eign P o l ic y